Administrative Law Review on The Enforcement of Kampar District Regulation Number 8 Of 2017 By The Satuan Polisi Pamong Praja Against The Circulation of Alcoholic Beverages - Hafiz Sutrisno; Fakhry Firmanto (International Journal of Science and Environment (IJSE), 2025)
This study aims to examine and analyze the implementation of the authority of the Satuan Polisi Pamong Praja (Satpol PP) of Kampar District in enforcing Kampar District Regulation Number 8 of 2017 concerning Public Order and Tranquility in relation to the circulation of alcoholic beverages (tuak), as well as to identify the factors that hinder its implementation. This research uses a juridical-empirical research method with an administrative law approach, where data is collected through field studies and literature reviews. The research findings indicate that the Satuan Polisi Pamong Praja of Kampar District has carried out its functions and authority in enforcing this regulation through activities such as law enforcement, socialization, and actions against violations related to the circulation of tuak. However, in practice, there are still several obstacles, including limited human resources and infrastructure, low public awareness, and weak coordination between relevant agencies. From an administrative law perspective, the law enforcement practices carried out by Satpol PP Kampar have complied with the principles of  bestuur recht  or good governance law, although its effectiveness needs to be improved through stronger technical regulations, enhanced capacity of officials, and increased community participation in supporting the enforcement of the District Regulation.